DEVELOPING HOLISTIC CARE MODEL: THE PHYSICAL WELLBEING OF ELDERLY BASED ON SOCIAL SUPPORT AND CHARACTERISTIC - Wiliyanarti, Pipit Festi; Asri, Asri; Putra, Kusuma Wijaya Ridi (Public Health of Indonesia, 2018)
Background: Elderly experiences with degenerative process in their life spam and physical condition as well as their ability to adopt with their environment. Those conditions will influence the achievement of elderly wellbeing.Purpose: This study aims to examine physical wellbeing in elderly based on social support and elderly characteristic.Method: This study employed cross-sectional survey design. The population was elderly who lived in east Surabaya. One hundred and ten of elderly were recruited. Their age was more than sixty years old, living with their family and under Medokan Ayu Public Health Center supervision. Multi stage random sampling was performed. The research instrument was physical wellbeing including elderly autonomy, cognitive, complaining about physical and disease as well. Structural Equation Modeling with Partial Least Square (SMART PLS) was used to analyze the data.Results: The research results showed that majority of emotional support in social support variable was good (98%). The majority of instrumental support was good (88.18%). Social wellbeing has significant relationship with the elderly physical wellbeing (p 0.312, t-statistic: 4.420, t-table: 1.65), elderly characteristic of holistic care (0.178, t-statistics 2.422, t-table: 1.65), and elderly characteristic of physical health (0.140. t-statistic 1.790, t table.1.65).Conclusion: Social support influences the physical wellbeing of elderly.